Analisis Pengaruh BI-Rate, Kurs Rupiah dan Laba Akuntansi terhadap Indeks Harga Saham Gabungan (Literature Review) - Nurwidina Rahayu; Rudi Sanjaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of BI Rate, Rupiah exchange rate, and accounting profit on the Composite Stock Price Index (IHSG) in Indonesia. As one of the main indicators in the capital market, IHSG reflects the overall stock market performance and is influenced by various macro and micro economic factors. BI Rate as the reference interest rate, Rupiah exchange rate as an indicator of currency exchange rate, and accounting profit as a measure of company performance have high relevance to the movement of IHSG. This study uses a literature review method by referring to various previous studies that discuss the relationship between these variables. The results of the analysis show that the three variables have a significant influence on IHSG, both directly and indirectly. BI Rate and Rupiah exchange rate affect IHSG through financial market mechanisms, while accounting profit is more related to investment decisions and individual company performance. These findings provide insight for investors, policy makers, and academics to understand the dynamics of the relationship between economic indicators and stock market performance in Indonesia.